Playground utilization: a study on urban, community and neighborhood park playgrounds in Manhattan, Kansas - Yao, Kanglin (Kansas State University, 2015)
Children’s play is partially satisfied through provision of public playgrounds with manufactured playground equipment in urban settings in the U.S., however, manufactured playground equipment is often criticized for its monotonous play equipment and is considered to be the primary cause of low playground utilization and dissatisfaction by many researchers (Hart, 2002; Beckwith, 2000; Cunningham & Jones, 1999; Davies, 1996; Masters, 2011). This study selected an urban park playground, a community playground, and a neighborhood park playground with manufactured equipment in the city of Manhattan as study sites. The purpose of this study is to examine utilization of the current playground areas and equipment—specifically by examining playground satisfaction levels and utilization frequency, and playground equipment satisfaction and utilization frequency to reveal playground utilization issues. A playground field audit and an on-site visitor survey were used to collect data. This study found (a) study playgrounds are underutilized among 6-to-10 and 11-to-15 age groups, (b) correlations exist between play equipment utilization frequencies and satisfaction ratings for most play equipment, and (c) no correlation exists between playground utilization frequency and playground satisfaction ratings. Results also revealed that (d) rare and occasional playground visitors are more likely to be attracted to play equipment with moving parts, higher physical challenges, and creative designs. Playground utilization rates are at current levels partially due to the rigid demand for playground use and play equipment. Although this study showed that 57% of survey participants were satisfied with the manufactured play equipment overall, play equipment should still be carefully selected and installed in consideration of different age groups, and visitors’ needs and characteristics; and more creative and cutting-edge play equipment should be considered for future playground improvements.
Keywords: Public playgrounds; Park playgrounds; Manufactured playground equipment; Manhattan, KansasPlayground utilization; Land Use Planning (0536)